Political participation, social inequalities, and special veto powers. Issue 3 (3rd May 2016) - Jörke, Dirk
Abstract : The retreat of socially disadvantaged people from the democratic process, which can be observed for some time now, is a symptom of the decreasing ability of Western societies to integrate its citizenry. This retreat poses a serious threat to democracy and must be regarded as a feature of a post-democratic constellation. It not only runs counter to the core democratic principle of political equality, but also has a tendency to strengthen the decline of social equality. Against this background, the article discusses alternative ways of participation which aim to reintegrate socially disadvantaged people in the democratic process. In this light, the author argues in favor of the idea of granting veto rights to disadvantaged people and concludes that it is fruitful to work within the contours of experimental democracy.